Normativna načela kot dejavnik mestnega razvoja (na primeru Ljubljane) - Ogorelec, Breda (Geografski vestnik, 1988)
Studies in urban morphology can either deal with the spatial charasteristics of the urban structure or with the causes which contribute to forming and modifying the physical structure of the city. The main determinants of structures and processes in a city are political system, technology, stage of development of national economy and normative principles. Urban geographers have paid almost no attention to the one mentioned last. Regulation became necessary, when the freedom of building became an obstacle or even a treath to the development of a city as a whole (both to spatial growth and to development of city functions, eg. healthy housing, traffic, security). Ljubljana received its building regulations in the end of the 19th century, the regulation plan (1896) being the only document in legal form until the Master plan of Ljubljana was accepted in 1966. The building orders contained paragraphs, which regulated the road width, height of buildings, maximum built-up-area index, design of public spaces etc. Case studies of the street pattern, building lines and building systems show, that the influence of normative principles (dating from the turn of the centuries) on urban forms was considerable. This is not true for the last four decades.
Keywords: geografija; geography; mesta; morfologija; morphology; regional planning; regionalno planiranje; urban design; urbanistično oblikovanje